JOGINĖS PERCEPCIJOS (YOGIPRATYAKṢA) KONTROVERSIJA INDIŠKOS EPISTEMOLOGIJOS KONTEKSTE. - Beinorius, Audrius (Problems / Problemos, 2017)
The article is dedicated to the analysis of the nature of yogic or supernormal perception (yogipratyaka, yogijñāna) in the context of Indian epistemology. By relying on the primary Sanskrit sources of Indian philosophical schools (darśana) and contemporary critical studies the questions are raised: what role is granted to it in the general Indian epistemological scheme (pramāavada)? How yogic perception is described and philosophicaly legitimated? How it is scholastically verified and validated and what kind of controversy was going on among different philosophical schools? On what arguments such perception is refused by orthodox Mīmāsā school? A combined - textological semantic, hermeneutical and comparative - methodology is applied. Conclusion is made that yogic perception is recognized and integrated into general scheme of knowledge by almost all Indian schools, though they give different accounts of it. A radical scepticism and refutation of this kind of perception is displayed by the representative of vedic hermeneutics and ritualistic exegesis - Kumārila Bhaṭṭa (7 AD) of Mīmāsā school. However, what the followers of this school denied was not the potentiality of the yogic perception itself, but consistency of logical argumentation, the ability of transparent transmission of such knowledge to others, and the validity of such experience in the legitimisation of divine revelation (śruti).